2021
DOI: 10.1021/acs.jafc.1c03992
|View full text |Cite
|
Sign up to set email alerts
|

Targeted and Nontargeted Metabolomics of Amino Acids and Bioactive Metabolites in Probiotic-Fermented Unhopped Beers Using Liquid Chromatography High-Resolution Mass Spectrometry

Abstract: Beer is one of the most popular beverages in the world. The increased popularity of craft beers has led to the development of unique beers that are alcohol-free, gluten-free, low calorie, or with functional properties through fermentation with probiotic microorganisms. In this study, functional unhopped beers were evaluated by utilizing probiotics (Lacticaseibacillus paracasei Lpc-37 and ibSium Saccharomyces cerevisiae CNCM I-3856) as starter cultures. The metabolites produced by probiotics were investigated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…DPPH radical scavenging capacity was determined as described previously ( 21 , 22 ). The ABTS radical scavenging capacity was determined as described previously ( 23 , 24 ), with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…DPPH radical scavenging capacity was determined as described previously ( 21 , 22 ). The ABTS radical scavenging capacity was determined as described previously ( 23 , 24 ), with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…22 Furthermore, targeted and nontargeted metabolomics analyses have revealed that synergistic effects of yeast−bacteria interactions led to further enrichment of amino acids derivatives in beer fermentation. 23 Thus, the interaction of D. hansenii with CNS and LAB may promote the accumulation of branched-chain esters and indole derivatives, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…hansenii in fermented sausages . Furthermore, targeted and nontargeted metabolomics analyses have revealed that synergistic effects of yeast–bacteria interactions led to further enrichment of amino acids derivatives in beer fermentation . Thus, the interaction of D.…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, the use of AQC derivatization has been extended to the analysis of non-standard amino acids, metabolites with amine moieties, and N -glycans. 12–14 Due to the flexibility of the detection device coupled to the LC, high sensitivity, good chromatographic separation, and high selectivity, AQC derivatization has been used in a wide range of application areas including the analysis of neurotransmitter amino acids, 15 characterizing the nutritional value of food and beverage, 16,17 and even soil amino acid analysis. 18…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, the use of AQC derivatization has been extended to the analysis of non-standard amino acids, metabolites with amine moieties, and N-glycans. [12][13][14] Due to the exibility of the detection device coupled to the LC, high sensitivity, good chromatographic separation, and high selectivity, AQC derivatization has been used in a wide range of application areas including the analysis of neurotransmitter amino acids, 15 characterizing the nutritional value of food and beverage, 16,17 and even soil amino acid analysis. 18 Aer AQC derivatization, the hydrophobic tag allows good chromatographic retention and separation of amino acids with different polarities on a reverse phase C18 column under generic chromatography conditions thereby enabling easy LC method development.…”
Section: Introductionmentioning
confidence: 99%